Peningkatan Kompetensi Digital Melalui Edukasi Pengelolaan Data Geospasial bagi Pemerintah Desa Wonoayu, Kecamatan Pilangkenceng - Saifulloh Saifulloh; Pratiwi Susanti; Moch Ali Murtadlo; Muhammad Rizal Permana (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
The transformation of villages into digital villages requires the availability of accurate and integrated data, one of which is geospatial data. Wonoayu Village, Pilangkenceng District, still faces problems such as overlapping land use and limited well-documented geospatial data. This community service activity aims to improve the digital competence of village officials through education on geospatial data management and the practice of creating analog maps using the QGIS application. The implementation method includes partner needs analysis, material preparation, training implementation through interactive lectures, technical demonstrations, hands-on practice, and evaluation using pre- and post-tests. The activity participants consisted of eight Wonoayu Village officials. The results of the activity showed an increase in participants' understanding of basic geospatial concepts, as indicated by an increase in the evaluation score from 72 in the pre-test to 85 in the post-test. In addition, participants were able to process spatial data, digitize it, and produce simple thematic maps that include the coordinates of village officials, educational institutions, and UMKM. This activity has a positive impact on the village's readiness to support data-based development planning and is the first step in realizing a sustainable digital village.